Effect of Sea Surface Temperature and Chlorophyll-a On the Catch of Yellowfin Tuna (Thunnus albacares) in The Waters of North Maluku, Indonesia - Muksin, Darmiyati; Rumagia, Faizal; Syukur, Kartina; Abubakar, Salim; Kadir, Irwan Abdul; Taeran, Imran; Darmawaty, Darmawaty; Kaidati, Bahar (Universitas Diponegoro, 2025)
The waters of North Maluku, abundant in nutrients and ocean currents, provide an ideal habitat for yellowfin tuna (Thunnus albacares), indicating a healthy marine ecosystem. Tuna, an oceanic pelagic species that migrates with ocean currents, is affected by sea surface temperature (SST) and chlorophyll-a plays an important role in determining yellowfin tuna fishing grounds. This study aims to analyze the spatial and temporal distribution of SST and chlorophyll-a concentration in North Maluku waters and analyze the relationship between SST, chlorophyll-a, and tuna catches. The present study employed both descriptive and quantitative analysis methods to examine the relationship between sea surface temperature, chlorophyll-a, and yellowfin tuna catch. The result shows that the temporal fluctuations in the highest recorded SST were seen in the 2021 transitional season, and the lowest in the 2019 East season. Chlorophyll-a concentrations also showed fluctuations, with the highest value recorded in the 2019 East season and the lowest in the 2020 second transitional season. There is an inverse correlation between SST and chlorophyll-a, with low SST tending to be accompanied by high chlorophyll-a concentrations. The decline in chlorophyll-a concentration can be attributed to various factors, including nutrient availability, sunlight intensity, and water temperature. About 17.48% of the catch of yellowfin tuna (Thunnus albacares) in North Maluku waters is influenced by SST and chlorophyll-a while the rest is influenced by other factors. This indicates that other factors play an important role in determining the catch of yellowfin tuna in North Maluku waters.